EFEKTIVITAS PENYULUHAN DENGAN MEDIA VIDEO DALAM MENINGKATKAN PENGATAHUAN DAN FREE PLAQUE SCORE PADA MURID TUNAGRAHITA DI SLBN 1 KOTA JAMBI - Sukarsih Sukarsih; Aida Silfia; Ainun Mardiah (Poltekkes Kemenkes Jambi, 2022)
Background: Mentally retarded children are children who are retarded in their mental development, so they experience obstacles in doing something work compared to other children of the same age. The aim of the study was to determine the effectiveness of counseling with video media in increasing knowledge and free plaque scores for mentally retarded students at SLBN 1 Jambi City. Methods: This study was a quasi-experimental study with the pre-test and post-test group design. The sample is SLBN 1 Jambi City students with mental retardation, totaling 40 people. The sampling technique used was the purposive sampling method. Result: There was an increase in knowledge of mentally retarded students at SLBN 1 Jambi City with high criteria having increased from 25% to 65% after receiving intervention. The average Free Plaque Score for mentally retarded students at SLBN 1 Jambi City increased from 26.23% to 82.85% after receiving intervention. The p-value of 0.000 <0.05 means that there is a significant difference between the value of knowledge and the Free Plaque Score before and after the intervention Conclusion: Counseling using video media is effective in increasing knowledge and the Free Plaque Score for mentally retarded students at SLBN 1 Jambi City.